High School Chemistry Learning: The Correlation Between Students' Critical Thinking and Self-Efficacy - Simorangkir, Agustina; Raidil, Muhammad (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This study aimed to investigate the relationship between critical thinking skills and self-efficacy in high school chemistry learning. This research investigates the correlation between students' critical thinking skills and their self-efficacy. Conducted at a senior high school in Jayapura, the research involved a sample of 96 students, selected using a random sampling technique. Utilizing a quantitative approach with a correlational research design, data were collected through standardized instruments measuring students’ critical thinking and self-efficacy. The instruments used were a self-efficacy questionnaire and a critical thinking skills test in the form of open-ended two-tier multiple-choice questions. The reliability of the critical thinking test was 0.850. The validity test of the self-efficacy questionnaire showed infit and outfit MNSQ values ranging from 0.77 to 1.30 using QUEST, with a reliability coefficient of 0.71. The data were analyzed using descriptive statistics using the Pearson correlation test to determine the correlation between students’ critical thinking skills and selthe f-efficacy. The analysis revealed a significant positive correlation between the two variables, indicating that students with higher self-efficacy tend to demonstrate stronger critical thinking skills. Furthermore, the implications of this research align with the United Nations’ Sustainable Development Goals (SDG 4 on Quality Education, SDG 9 on Industry, Innovation, and Infrastructure, and SDG 12 on Responsible Consumption and Production), highlighting the contribution of chemistry education to sustainable development through enhanced critical thinking skills.